2013
DOI: 10.1177/2158244013507269
|View full text |Cite
|
Sign up to set email alerts
|

Toward a New Understanding of Virtual Research Collaborations

Abstract: Virtual research collaborations (VRCs) have become an important method of conducting scientific activity; however, they are often regarded and treated as traditional scientific collaborations. Their success is measured by scholarly productivity and adherence to budget by funding agencies, participating scientists, and scholars. VRCs operate in complex environments interacting with other complex systems. A holistic (or organicist) approach is needed to make sense of this complexity. For that purpose, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…To address this research gap, we examined a viable EE: the Zhongguancun EE in Beijing, China. Our study revealed six interrelated complexity properties of the Zhongguancun EE that are in line with the main properties that a CAS possesses (Aydinoglu, 2013;Peltoniemi, 2006;: a large number of selforganized agents, nonlinear interactions, (in)sensitivity to initial conditions, adaptation to the environment, emergence of successful entrepreneurial firms, and coevolution. Moreover, the synthesis of six interrelated complexity properties provides a better understanding of how the Zhongguancun EE maintains its viability through different developmental stages.…”
Section: Discussionsupporting
confidence: 74%
“…To address this research gap, we examined a viable EE: the Zhongguancun EE in Beijing, China. Our study revealed six interrelated complexity properties of the Zhongguancun EE that are in line with the main properties that a CAS possesses (Aydinoglu, 2013;Peltoniemi, 2006;: a large number of selforganized agents, nonlinear interactions, (in)sensitivity to initial conditions, adaptation to the environment, emergence of successful entrepreneurial firms, and coevolution. Moreover, the synthesis of six interrelated complexity properties provides a better understanding of how the Zhongguancun EE maintains its viability through different developmental stages.…”
Section: Discussionsupporting
confidence: 74%
“…As Landström (, p. 316) points out, “the research community on entrepreneurship research has grown significantly during the past two decades; at the same time we can identify a large number of core and contributing authors who have led the research into a more mature field of research.” They have been highly influential in the field's development and in setting the research agenda. This study provides empirical evidence to some extent concerning “how interacting scholars adapt and co‐evolve over time, and who, through their interaction, produce novel and emergent order in creative and spontaneous ways.” (Aydinoglu , p. 4)…”
Section: Discussionmentioning
confidence: 99%
“…Tol (2009) found this to be true for citations of economists, as did Ho (2013) for social workers. Further, the complex adaptive nature of networks (Aydinoglu, 2013) has made networks unsuitable for linear analysis. Thus, visual and tabular analyses were used in the present investigation.…”
Section: Complexity Theory Research Methods and Coauthor Networkmentioning
confidence: 99%